I-131 Treatment of Graves' Disease in an Unsuspected First Trimester Pregnancy; the Potential for Adverse Effects on the Fetus and a Review of the Current Guidelines for Pregnancy Screening. (2nd March 2010) - Tran, Phuong; DeSimone, Shane; Barrett, Mark; Bachrach, Bert
Abstract : Graves' disease is a thyroid-specific autoimmune disorder in which the body makes antibodies to the thyroid-stimulating hormone receptor leading to hyperthyroidism. Therapeutic options for the treatment of Graves' disease include medication, radioactive iodine ablation, and surgery. Radioactive iodine is absolutely contraindicated in pregnancy as exposure to I-131 to the fetal thyroid can result in fetal hypothyroidism and cretinism. Here we describe a case of a female patient with recurrent Graves' disease, who inadvertently received I-131 therapy when she was estimated to be eight days pregnant. This was despite the obtaining of a negative history of pregnancy and a negative urine pregnancy test less than 24 hours prior to ablation. At birth, the infant was found to have neonatal Graves' disease. The neonatal Graves' disease resolved spontaneously. It was suspected that the fetal thyroid did not trap any I-131 as it does not concentrate iodine until 10 weeks of gestation.